The Effect of Quality, Communication and Outputs of Marketing Channel of Cianjur Pandanwangi Rice on Consumer Trust in Java West Marketing Area - Endah Lisarini; Eddy Yusuf; Sutina Sutina (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
The objectives of this study are to examine: 1) the influence of product quality, marketing communications and marketing distribution outlet or output channel on consumer trust; 2) dominant factors that influence consumer trust in Cianjur Pandanwangi rice. A descriptive verification method was conducted in order to get an idea of the four dimensions of product quality, the four dimensions of marketing communications and the three dimensions of the marketing distribution channel in building consumer trust in Cianjur Pandanwangi rice. Consumer trust is reflected in transparency, incentives and partnerships. Semantic Differential with numerical rating scale was used to measure 300 responses collected by cross sectional survey. Data processing was conducted by SEM AMOS 22. The result of analysis shows that product quality and distribution channel have significant effects on consumer trust, while marketing communication channel does not give significant influences on consumer trust. Successive dimensions of quality that have significant influences on consumer trust include the rice glutinious texture, purity, color grain of rice and aroma while the output of distribution channel influential to consumer trust includes the diversity of sales volume and easiness to get Pandanwangi rice. These conditions indicate that consumer confidence is not only built from good product quality and ease of availability but also from appropriate communication media reaching the right target. Consumers will trust Pandanwangi rice is purely from Cianjur if it is communicated clearly and transparently.Keywords: marketing mix, consumer value, cianjur pandanwangi rice